Modern Construction Management. - Harris, Frank, 1944-; McCaffer, Ronald; Edum-Fotwe, Francis (Chichester, West Sussex : Wiley-Blackwell, 2013)
This edition has been thoroughly revised and updated to cover the latest practices in PFI/PPP, risk management, supply networks, sustainability, lean construction, KPIs and value management.
Previous ed.: Oxford: Blackwell, 2006.
Includes bibliographical references and index.
Keywords: Construction industry -- Management; Technology